2019
DOI: 10.30880/jtet.2019.11.01.008
|View full text |Cite
|
Sign up to set email alerts
|

An Effectiveness of High Order Thinking Skills (HOTS) SelfInstructional Manual for Students’ Assignment Achievement

Abstract: High Order Thinking Skills (HOTS) is an important aspect of teaching and learning. An individual's thinking can affect learning ability, learning speed and effectiveness of learning. The weakness in implementing HOTS is one of the reasons for a student not being creative in solving all the problems that arise. The purpose of this study was to evaluate the effectiveness of HOTS's Self-Instructional Manual (SIM) in teaching and learning for assignment achievement among polytechnic students. This study uses a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
3
Order By: Relevance
“…All these instructions guided students to discover and generate ideas across different categories and develop unconventional notions. The questions within the creative thinking category prompted students to identify problems and devise solutions by engaging in creative and innovative thinking within real-life situations (Priyatni & Martutik, 2020;Hamdan et al, 2019). Research results conducted by Suwandi et al (2021) indicated that thinking skills evaluated in the National Examination questions involved elaborating on points of view, determining main ideas and causes of conflict in literary texts, describing character traits, and identifying relevant paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…All these instructions guided students to discover and generate ideas across different categories and develop unconventional notions. The questions within the creative thinking category prompted students to identify problems and devise solutions by engaging in creative and innovative thinking within real-life situations (Priyatni & Martutik, 2020;Hamdan et al, 2019). Research results conducted by Suwandi et al (2021) indicated that thinking skills evaluated in the National Examination questions involved elaborating on points of view, determining main ideas and causes of conflict in literary texts, describing character traits, and identifying relevant paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…Las habilidades de pensamiento superior se pueden definir como los procesos de análisis, síntesis y evaluación que realiza la persona, en este caso el alumnado, con el objetivo de aprender, y que permite aplicar conocimientos, habilidades y valores de cara a resolver problemas, tomar decisiones, innovar o crear algo (Lembaga Peperiksaan, 2014; citado en Hamdan et al, 2019). Las habilidades de pensamiento superior se pueden considerar operaciones mentales organizadas y coordinadas en función de las cuales procesamos la información que captamos, lo que permite el desarrollo de las capacidades intelectuales, psicomotoras y/o socio afectivas, así como la solución de problemas y toma de decisiones con respecto a la vida diaria y la carrera profesional del estudiantado.…”
Section: Introductionunclassified
“…Las metas fundamentales de la educación universitaria son la formación de habilidades de pensamiento de orden superior, el desarrollo de la capacidad crítica y la validación o la producción de teorías capaces de resolver problemas significativos (Duque, 2006). Apoyándose en el pensamiento de orden superior, las instituciones de educación superior desempeñan un papel importante en la producción de una generación joven con las habilidades necesarias para ser competitiva en la industria y ser una fuente de crecimiento económico en una sociedad global que necesita ser sostenible cada vez más (Hamdan et al, 2019). El profesorado debe enseñar las capacidades o las habilidades para pensar críticamente, fomentado las habilidades de pensamiento de orden superior, con el objetivo de mejorar su capacidad para pensar razonadamente, para responder preguntas cada vez más difíciles o resolver casos-problemas más complicados.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Learning is an activity carried out by students and teachers (Hamdan et al, 2019;Stošić, 2015). Learning will consist of several interacting components.…”
Section: Introductionmentioning
confidence: 99%